2023
DOI: 10.1111/1744-7917.13253
|View full text |Cite
|
Sign up to set email alerts
|

Both host and diet shape bacterial communities of predatory mites

Abstract: Microbial communities, derived from food, ambient, and inner, can affect host ecological adaption and evolution. Comparing with most phytophagous arthropods, predators may have more opportunities to develop specific microbiota depending on the level of prey specialization. To explore how diet sources affect host microbial communities and vary across predator species, we considered 3 types of predators from Phytoseiidae (Acari: Mesostigmata): polyphagous (Amblyseius orientalis Ehara, Neoseiulus barkeri Hughes, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The two species with similar feeding types are both carnivorous and were dominant species in their respective benthic habitats, so it was speculated that they have the same dietary niche. Dietary niches, as a primary influence, impact the gut microbiota by providing specific nutrients and substrates that select certain microbial species, thus affecting overall community structure ( 86 ), as observed in the cichlid species complex ( 86 , 87 ). Our previous studies revealed significant differences in gut microbes among ophiuroids with varying feeding types, while the gut microbes of two carnivorous ophiuroids ( Stegophiura sladeni and O. sarsii vadicola ) were similar ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The two species with similar feeding types are both carnivorous and were dominant species in their respective benthic habitats, so it was speculated that they have the same dietary niche. Dietary niches, as a primary influence, impact the gut microbiota by providing specific nutrients and substrates that select certain microbial species, thus affecting overall community structure ( 86 ), as observed in the cichlid species complex ( 86 , 87 ). Our previous studies revealed significant differences in gut microbes among ophiuroids with varying feeding types, while the gut microbes of two carnivorous ophiuroids ( Stegophiura sladeni and O. sarsii vadicola ) were similar ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…qPCR using SYBR Mixture (with ROX) in FQD-96A with the following program: initial denaturation at 95 ℃ for 10 min, followed by 40 cycles at 95 ℃ for 20 s, 60 ℃ for 20 s and 72 ℃ for 30 s. The expression quantity of the gene was calculated using 2 −ΔΔCT method (Livak and Schmittgen 2001). Each sample had three technical replicates and β-actin gene was used as reference gene (Bi et al 2019;Yan et al 2024).…”
Section: Spatiotemporal Expression Patterns Of Hormone-related Genesmentioning
confidence: 99%